2021
DOI: 10.3390/ma14040889
|View full text |Cite
|
Sign up to set email alerts
|

Cell Behavior of Primary Fibroblasts and Osteoblasts on Plasma-Treated Fluorinated Polymer Coated with Honeycomb Polystyrene

Abstract: The development of new biocompatible polymer substrates is still of interest to many research teams. We aimed to combine a plasma treatment of fluorinated ethylene propylene (FEP) substrate with a technique of improved phase separation. Plasma exposure served for substrate activation and modification of surface properties, such as roughness, chemistry, and wettability. The treated FEP substrate was applied for the growth of a honeycomb-like pattern from polystyrene solution. The properties of the pattern stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…Milled acrylic was slightly pro-osteoblastic at all time points. In another study examining the cytotoxicity of different surface treatments of composite, there was a trend towards a pro-osteoblastic phenotype [ 59 ], consistent with our results. We separately evaluated the contact and proximity effects of each material for fibroblasts and osteoblasts and provided robust, fundamental data, which warrants further studies such as in vitro mechanistic studies and animal studies.…”
Section: Discussionsupporting
confidence: 91%
“…Milled acrylic was slightly pro-osteoblastic at all time points. In another study examining the cytotoxicity of different surface treatments of composite, there was a trend towards a pro-osteoblastic phenotype [ 59 ], consistent with our results. We separately evaluated the contact and proximity effects of each material for fibroblasts and osteoblasts and provided robust, fundamental data, which warrants further studies such as in vitro mechanistic studies and animal studies.…”
Section: Discussionsupporting
confidence: 91%
“…After additional cultivation, 96 h post-seeding, cell proliferation was obvious on each evaluated sample. The lowest number of cells was detected on the unmodified FEP sample, which is consistent with our previous results, e.g., [58][59][60]. The cell number was increased on plasma-treated FEP 96 h after seeding when compared to pristine FEP.…”
Section: Cytocompatibilitysupporting
confidence: 92%
“…The very first polymers used by the breath figure technique were star homopolymers. Thanks to the spherical shape that they form in solution, they can create highly ordered structures [ 27 ] ( Figure 3 ). However, it was later shown that even linear homopolymers can form ordered porous films [ 28 ] and their use is undoubtedly the most widespread strategy.…”
Section: Polymeric Honeycombsmentioning
confidence: 99%
“…Half a century later, dew formation, whose thermodynamic and kinetic aspects are key to understanding BF formations in polymeric materials, was studied theoretically and experimentally [ 44 ]. A breakthrough in the application of BF was achieved in 1994, when Francois et al, came up with the fabrication of polymer films with a highly ordered HCP morphology using condensed water droplets, which served as a dynamic template [ 27 ]. Star PS or polystyrene-b-polyparaphenylene dissolved in carbon sulfide was used in the experiment.…”
Section: Preparation Of Hcp Structuresmentioning
confidence: 99%